THE PREDICTIVE SIGNIFICANCE OF EOSINOPHILIA IN PERIPHERAL BLOOD IN PATIENTS WITH HODGKIN LYMPHOMA - Sretenović, Snežana; Jovanović, Danijela; Dragović, Ana; Aleksić, Sanja (Srpski medicinski časopis Lekarske komore, 2026)
Introduction/Objective: Hodgkin lymphoma (HL) is a rare neoplasm of the lymphatic system and is one of the most common cancers in the young adult population. Histopathologically, 95% of Hodgkin lymphoma is classic Hodgkin lymphoma (cHL). Eosinophilia, both peripherally and in tissues, is relatively common in patients with HL, especially in the nodular sclerosis and mixed cellularity subtypes. Its presence indicates a complex interaction between tumor cells and the immune system. In addition to eosinophilia present in the tissue sample, eosinophilia is also detected in the peripheral blood. The study aimed to analyze HL patients by sex, age, clinical stage, the International Prognostic Score (IPS), and B symptoms, as well as to determine the association between tumor mass size and the complete blood count, erythrocyte sedimentation rate (ESR), the C reactive protein (CRP) level, the clinical stage, and the IPS, with special reference to the significance of eosinophilia in peripheral blood as a predictor of tumor mass size and therapeutic response. Materials and methods: A retrospective analysis of 58 new cases of HL, diagnosed and treated at the Clinic for Hematology of the University Clinical Center Kragujevac, was performed between December 31, 2018, and December 31, 2023. Data was obtained from written medical records. The initial blood laboratory parameters at diagnosis were analyzed, and the therapeutic response was assessed after the first-line therapy was administered. IBM SPSS Statistics, Version 23, software was used for statistical data processing. Statistical significance was defined at p < 0.05. Results: At presentation, the observed population had advanced disease – CS III (27.6%) and CS IV (39.7%); B symptoms were present in 76% of the patients, and a high IPS was registered in 48.3% of the subjects. Bulky mediastinal mass was present in 48.3% of patients, while 34.3% of patients presented with nonmediastinal localization. No correlation was found between the leukocyte count, the eosinophil count, the hemoglobin level, the erythrocyte sedimentation rate, CRP values, the clinical stage, IPS, and the maximum diameter of the measured lymph nodes (p > 0.05). However, the analysis showed a statistically significant association between eosinophilia and therapeutic response (p = 0.024), indicating its potential prognostic significance. Conclusion: Peripheral blood eosinophilia was shown to be a potential predictor of therapeutic response, but not a predictor of tumor mass size. Clinical and radiological diagnostics remain the standard for assessing tumor burden.